KINERJA PIRANTI PENDINGIN TERMOAKUSTIK GELOMBANG BERDIRI DAN GELOMBANG BERJALAN MENGGUNAKAN STACK PORI ACAK - ASMARA, PUTIH ([Yogyakarta] : Universitas Gadjah Mada, 2015)
It has been done an experiment of the influence of arbitrarily shaped pores stacks for the performance of standing-wave and traveling-wave termoacoustic refrigerator device. The arbitrarily shaped pores materials is dacron and wool which have the length variations of 6 cm, 7 cm, 8 cm and the density variations of 5 kg/m3, 10 kg/m3, 15 kg/m3. On standing wave engine, the resonance frequency have been shifted from the calculated resonance frequency as consequence of existance of the arbitrarily shape pores stack. Increasingly of the density of stack makes increasingly of the resonance frequency shifted. The largest temperature decrease of the cold side is (13,6±0,1) °C when using dacron stack, with 8 cm of length, 5 kg/m3 and 10 kg/m3 of density. Using the wool stack the temperature decrease of the cold side reached (18,1±0,1) °C, the with 7 cm of length and 10 kg/m3 of density. The optimum power which makes the largest temperature decrease of the cold side is 60 W. On the traveling wave engine using wool stack of 7 cm of length and 10 kg/m3 of density, resonance frequency is (60±1) Hz. The largest temperature decrease cold side is around (11,4±0,1) °C at 60 W of power. Coeficient of performance by using the wool stack 7 cm of length and 10 kg/m3 of density, when applied the standing wave engine can reach 13,4, whereas the traveling wave engine can reach 21,6. Key words: arbitrarily shaped pores stack, density, standing wave engine, traveling wave engine,coeficient of performance, thermoacoustic